Luteolin Pretreatment Attenuates Hepatic Ischemia-Reperfusion Injury in Mice by Inhibiting Inflammation, Autophagy, and Apoptosis via the ERK/PPARα Pathway - Yuhui Jiang; Wenjuan Yang; Jiameng Ding; Jie Ji; Liwei Wu; Yuanyuan Zheng; Yan Li; Ziqi Cheng; Jie Zhang; Qiang Yu; Jiao Feng; Jingjing Li; et al. (PPAR Research)
Hepatic ischemia-reperfusion (IR) injury is a clinically significant process that frequently occurs in liver transplantation, partial hepatectomy, and hemorrhagic shock. The aim of this study was to explore the effectiveness of luteolin in hepatic IR injury and the underlying mechanism. BALB/c mice were randomly divided into six groups, including normal controls (NC), luteolin (50 mg/kg), sham procedure, IR+25 mg/kg luteolin, and IR+50 mg/kg luteolin group. Serum and tissue samples were collected at 6 and 24 h after reperfusion to assay liver enzymes, inflammatory factors, expression of proteins associated with apoptosis and autophagy, and factors associated with the extracellular signal-regulated kinase/peroxisome proliferator-activated receptor alpha (ERK/PPARα) pathway. Luteolin preconditioning decreased hepatocyte injury caused by ischemia-reperfusion, downregulated inflammatory factors, and inhibited apoptosis and autophagy. Luteolin also inhibited ERK phosphorylation and activated PPARα.